Formación Docente Socio Comunitaria en la Carrera de Educación Inicial de la Universidad Nacional de Educación - Gisselle Tur Porres (Revista Scientific, 2019)
The Initial Education career of the National University of Education reconsiders the training of teachers-researchers in the Ecuadorian and regional context, which facilitates teaching-learning processes with children from 0 to 5 years old, as actors of transformation in territory through the attention and resolution of problems in the educational field, from a framework of equity, interculturality, inclusion, pedagogical and social innovation. In this sense, an analysis of the career in its socio-communitydimension is presented, according to the pedagogical foundations of the university, curricular elements and what the respective territory demands. The methodology used is part of the qualitative approach and documentary research. The theoretical contributions are based on the Social Management of Knowledge and the conceptions of connection with the collectivity according to Vallaeys (2014), Martínez (2011) and Santos (2004). The documentary review was carried out from the political, educational and social dimension, also revealed in institutional reports. From the analysis, it was possible to achieve the conceptual and contextual foundation of teacher training in the Initial Education career from and for a community-based dimension; its characterization and the advances and challenges of this process with emphasis on preprofessional practices as a dynamic scenario.La carrera de Educación Inicial de la Universidad Nacional de Educación replantea la formación de docentes-investigadores en el contexto ecuatoriano y regional, que facilite procesos de enseñanza-aprendizaje con niños/as de 0 a 5 años, como actores de transformación en territorio mediante la atención y resolución de problemas en el ámbito educativo, desde un marco de equidad, interculturalidad, inclusión, innovación pedagógica y social. En este sentido, se presenta un análisis de la carrera en su dimensión socio-comunitaria, según los fundamentos pedagógicos de la universidad, elementos curriculares y lo que demanda el territorio respectivo. La metodología empleada se enmarca en el enfoque cualitativo y en la investigación documental. Los aportes teóricos son fundamentados en la Gestión Social del Conocimiento y las concepciones de vinculación con la colectividad según Vallaeys (2014), Martínez (2011) y Santos (2004). La revisión documental se realizó desde la dimensión política, educativa y social, revelada además en informes institucionales. A partir del análisis fue posible lograr la fundamentación conceptual y contextual de la formación docente en la carrera de Educación Inicial desde y para una dimensión socio comunitaria; su caracterización y los avancesy desafíos de este proceso con énfasis en las prácticas preprofesionales como escenario dinamizador.